2012
DOI: 10.1177/0954409712467139
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of corrugated sheets in a railway vehicle's body structure by a multiple-requirement based selection process

Abstract: To simplify construction, reduce weight and improve mechanical properties, a sandwich panel substitution process is performed on corrugated sheets in the floor and roof of a rail vehicle car body. A requirement based selection is used to design the sandwich panels with the corrugated sheet mechanical characteristics as boundaries. Car body stiffness is evaluated by modal analysis. The derived panels reduce the mass of the car body by 600–700 kg. Results show the varying importance of the longitudinal, transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
(10 reference statements)
0
14
0
1
Order By: Relevance
“…They proposed to design the shape of the rib and the thickness distribution of the aluminum extruded carbody using a design process based on structural optimization. In 2012, David performed a sandwich panel substitution process to reduce the weight of corrugated sheets in the floor and roof of rolling stock carbodies [8].…”
Section: Introductionmentioning
confidence: 99%
“…They proposed to design the shape of the rib and the thickness distribution of the aluminum extruded carbody using a design process based on structural optimization. In 2012, David performed a sandwich panel substitution process to reduce the weight of corrugated sheets in the floor and roof of rolling stock carbodies [8].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the car body weight and improve the dynamic properties of the car body, a sandwich panel substitution process was performed on corrugated board of the floor of a rail vehicle car body by Wennberg et al, 9 and they found that the mass of car body could be reduced by 600-700 kg, and the varying importance of the longitudinal, transverse and shear properties of the floor panels can be improved. Hudson et al 10 performed a multiple objective optimisation of low mass and cost on composite sandwich panels for the interior floor structure of a metro car.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, the freight railway vehicles are designed in such a manner that significant attention has been given to lightweighting. 1,2,[22][23][24] This has been driven in the main by the consideration for reduced emissions and impact on the infrastructure.…”
Section: Introductionmentioning
confidence: 99%